การวิเคราะห์องค์ประกอบเชิงยืนยันสมรรถนะผู้ประกอบการของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาอุดรธานี: A Confirmatory Factor Analysis of Entrepreneurial Competencies of School Administrator Under The Secondary Educational Service Area Office Udon Thani - ทุ่งฝน, ณัฐชนก; อารีรัตน์ , วัลลภา (Journal of Humanities and Social Sciences (HUSOKKU), 2026)
The purposes of this research were: (1) to examine the components and indicators of entrepreneurial competencies of school administrators, and (2) to verify the goodness-of-fit of the entrepreneurial competency indicator model with empirical data. The sample consisted of 300 school administrators and teachers under the Secondary Educational Service Area Office Udonthani, selected through multi-stage random sampling. The research instrument was a five-point rating scale questionnaire with content validity indices ranging from 0.80 to 1.00 and a reliability coefficient of 0.905. Data were analyzed using Confirmatory Factor Analysis (CFA) with a computer-based statistical software program. The results revealed that the entrepreneurial competencies of school administrators comprised five main components: (1) innovative initiative, (2) risk management, (3) effective management, (4) entrepreneurial social skills, and (5) achievement motivation. Each component consisted of three indicators, resulting in a total of fifteen indicators. Furthermore, the structural validity analysis indicated that the entrepreneurial competency component model of school administrators demonstrated a good fit with the empirical data, as evidenced by the following indices: χ² = 91.60, df = 74, p-value = 0.081, RMSEA = 0.028, SRMR = 0.020, CFI = 0.996, and TLI = 0.994.